Neonatal screening for congenital adrenal hyperplasia. Issue 10 (October 1983) - Cacciari, E; Balsamo, A; Cassio, A; Piazzi, S; Bernardi, F; Salardi, S; Cicognani, A; Pirazzoli, P; Zappulla, F; Capelli, M
Abstract : Capillary blood samples from 42930 infants born in the Italian region of Emilia-Romagna were collected for 17-hydroxyprogesterone radioimmunoassays on days 2, 3, 4, 5, 6, and 7, or between days 7 and 15 of life. A microfilter paper method modified from that of Pang et al.1 was used for this assay. Pathologic values of 17-hydroxyprogesterone were found in 5 infants giving an incidence in this homogeneous Caucasian population of 1:8586. We also investigated 17-hydroxyprogesterone values in relation to the day of sampling and the possible correlation between 17-hydroxyprogesterone values and birthweight and gestational age. We concluded that neonatal screening for congenital adrenal hyperplasia caused by 21-hydroxylase deficiency was possible by this method and that the infants' maturity and the particular day of collection of the samples affect the values but not the validity of the screening.